Impact of body mass index on 90-day warfarin requirements: a retrospective chart review. (June 2021) - Soyombo, Bolanle M.; Taylor, Ashley; Gillard, Christopher; Wilson, Candice; Bailey Wheeler, Janel
Background: Rates of obesity continue to rise worldwide as evidenced in the 2017 Centers for Disease Control and Prevention (CDC) report that indicated over 35% of United States (US) citizens are obese, with Louisiana ranked as the fifth most obese state in America. Since large clinical trials tend to exclude obese patients, health care providers are faced with concerns of under- or overdosing these patients on warfarin. Methods: This retrospective chart review evaluated patients who reported to a community anticoagulation clinic for warfarin management between 1 June 2017 and 30 September 2017. Along with baseline demographics, chronic use of drugs that have clinically significant interactions with warfarin, social activity such as tobacco use and alcohol consumption, were collected. Body mass indexes (BMI) were collected and categorized according to the World Health Organization definitions as follows: Normal (BMI 18–24.9 kg/m 2 ), Overweight (25–29.9 kg/m 2 ), Obesity Class I (30–34.9 kg/m 2 ), Obesity Class II (35–39.9 kg/m 2 ), Obesity Class III (⩾40 kg/m 2 ). The primary outcome was the mean 90-day warfarin dose required to maintain "intermediate control" or "good control" of international normalized ratio (INR), stratified by BMI classifications. The secondary outcome was the time in therapeutic range (TTR) stratified by BMI classifications. Results: A total of 433 patient encounters were included in this study. There was a total of 43 encounters in the Normal BMI category, 111 Overweight encounters, 135 Obesity Class I encounters, 45 Obesity Class II encounters, and 99 Obesity Class III encounters. Approximately 63% of the study population were male, and over 90% the patients were African American. The Obesity Class I and Obesity Class II class required an average of 11.47 mg and 17.10 mg more warfarin, respectively, to maintain a therapeutic INR when compared with the Normal BMI category. These findings were statistically significant with p values of 0.007 and <0.001, respectively. Additionally, upon comparing the Overweight BMI category with the Obesity Class II category, there was a mean warfarin dose difference of 11.22 mg ( p  = 0.010) more in Obesity Class II encounters to maintain a therapeutic INR. In the secondary analysis of TTR, Overweight category encounters had the highest TTR, whereas encounters in the Normal BMI category had the lowest TTR. Conclusion: As BMI increases, there is an increased chronic warfarin requirement to maintain "intermediate control" or "good control" of INR between 2 and 3 in an ambulatory care setting.